Navigating early specialization sport: Parent and athlete goal-directed processes - Wall, J. M.; Pradhan, K.; Baugh, L. M.; Beauchamp, M. R.; Marshall, S. K.; Young, R. A. (Sport, Exercise, and Performance Psychology, 2020)
The purpose of this study was to describe the relational processes that exist between parents and athletes when engaged in an early specialization sport. Using an instrumental case study design, 5 parent-athlete (Mathlete age = 11.40 years) dyads in Canadian competitive figure skating represented cases for individual and collective analysis. Contextual action theory and the action-project method were used to identify and describe the naturally occurring projects (i.e., joint actions over time) of parents and athletes as they engaged in the transition together. Data were collected longitudinally over a total of 10 months and included video-recorded parent-athlete conversations, video feedback-supported recall of thoughts and feelings, and 6 months of biweekly self-report data collected through telephone interviews. Data analysis occurred simultaneously over the course of the study using transcripts, a coding system, and a form of member reflection. Final cross-case analyses highlighted pertinent themes across cases. Parent-athlete dyads` joint projects were grouped based on three common themes: negotiating school, sport, and extracurricular commitments; progressing toward skating goals; and maintaining a developmental focus, including tailoring involvement in skating to accommodate growth and development and prioritizing well-roundedness and personal development. The joint projects were embedded in the broader parent-child relationship project. This study presents a goal-directed and relational perspective on the transition to specialized training in Canadian competitive figure skating. Together, parents and athletes not only focused on negotiating the various commitments, demands on time, and expectations for progress in figure skating, they also accommodated and fostered nonsport development.